Development of E-modules Based on Articulate Storyline 3 - Kalyaningsih, Ima; Zamzam, Kenys Fadhilah (Program Studi Pendidikan Matematika Universitas PGRI Kanjuruhan Malang, 2025)
This research aims to craft an e-module developed using Articulate Storyline 3, focusing on integer concepts, specifically designed for seventh-grade junior high school students. Mathematics, as a crucial component of Indonesia's educational curriculum, is often perceived as complex and monotonous by students, necessitating innovative approaches in learning. This e-module is expected to emerge as a groundbreaking tool that stimulates students' enthusiasm in exploring the subject matter. To achieve this, the study adopts a Research and Development (R&D) approach, implementing the ADDIE model, which consists of initial analysis, conceptual design, development, real-world implementation, and comprehensive evaluation. Validation results indicate that the e-module achieves a remarkably high validity level of 95.19%, a practicality score of 83.33%, and an effectiveness rate of 87.85%. Beyond merely meeting validity criteria, the e-module is meticulously designed to ensure accessibility for students while proving to be a powerful tool in enhancing their academic performance. Thus, this Articulate Storyline 3-based e-module is envisioned as a revolutionary learning instrument—an engaging and interactive medium that supports the achievement of learning objectives related to integers at the junior high school level.